The Effect of Motivation, Promotion and Destination Image on Visitor Satisfaction Through Visiting Decisions as Intervening Variables at Saung Angklung Udjo Tourism Objects - Harmadi, Ashur; Nuryanto, Guyub; Binastuti, Sugiarti; Makmun, Makmun; Nuramalia, Dina (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study is to determine the effect of motivation, promotion, and destinaton image on visitor satisfaction through the decision to visit as an intervening variable at the Saung Angklung Udjo tourist attraction. The methods of analysis of this study used quantitative primary data, the test stages carried out are validity test, reliability test, and structural equation model (SEM). The data used in this study used a questionnaire instrument that was collected as many as 150 respondents. The sampling method in this study is non probability sampling with purposive ampling technique. Testing tools used SPSS and AMOS. The result of the study indicate that the motivation and destination image variables have a positive and significant effect on the decision to visit. The variables of promotion, destination image, and decision to visit have a positive and significant effect on visitor satisfaction. While the promotion variable does not have a positive and significant effect on decision to visit and the motivation variable does not have a positive and significant effect on visitor satisfaction.